Evaluation Of Financial Reporting Implementation Based On Isak 35 To Improve The Financial Performance Of Non-Profit Entities - qodadad nazer ali; Putra, Rediyanto (International Environmental Conferrence on Biosustainability Advancement, 2024)
This research aims to evaluate and implement the preparation of financial statements at the Al Ikhlas Magetan Foundation based on the Interpretation of Financial Accounting Standards (ISAK) 35. This research is a type of qualitative research. The data used uses primary data and secondary data obtained through interviews, observation, and documentation. Data analysis techniques in this research used the data analysis stages of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the research show that the financial management of the Al Ikhlas Magetan Foundation is still carried out simply. The report prepared by the Al Ikhlas Magetan Foundation is not in accordance with ISAK 35. The researcher reconstructed the financial statements of the Al Ikhlas Magetan Foundation and implemented ISAK 35 in the Foundation’s 2022 financial statements which consist of a statement of financial position, a statement of comprehensive income, a report on changes in net assets, a statement of cash flow cash, and notes to financial statements.